Inorganic Halide Perovskite Quantum Dots: A Versatile Nanomaterial Platform for Electronic Applications - Huang, Chien‑Yu; Li, Hanchen; Wu, Ye; Lin, Chun‑Ho; Guan, Xinwei; Hu, Long; Kim, Jiyun; Zhu, Xiaoming; Zeng, Haibo; Wu, Tom (Nano-Micro Letters, 2022)
Metal halide perovskites have generated significant attention in recent years because of their extraordinary physical properties and photovoltaic performance. Among these, inorganic perovskite quantum dots (QDs) stand out for their prominent merits, such as quantum confinement effects, high photoluminescence quantum yield, and defect-tolerant structures. Additionally, ligand engineering and an all-inorganic composition lead to a robust platform for ambient-stable QD devices. This review presents the state-of-the-art research progress on inorganic perovskite QDs, emphasizing their electronic applications. In detail, the physical properties of inorganic perovskite QDs will be introduced first, followed by a discussion of synthesis methods and growth control. Afterwards, the emerging applications of inorganic perovskite QDs in electronics, including transistors and memories, will be presented. Finally, this review will provide an outlook on potential strategies for advancing inorganic perovskite QD technologies. Highlights: 1 Research progress on inorganic perovskites quantum dots is reviewed from three aspects: physical properties, synthesis approaches, and electronic applications. 2 Inorganic perovskite quantum dots have been exploited as either the active layers or the additives in high-performance transistors and memories. 3 Challenges and outlook on future advancement of perovskites quantum dots-based electronics are elaborated.